2023
DOI: 10.1029/2022gl101773
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in the Seasonal Cycle of Madden‐Julian Oscillation Precipitation and Wind Amplitude

Abstract: The core region of MJO activity is located at low latitudes (e.g., 0°-15°) in the summer hemisphere (Hendon & Liebmann, 1990;Maloney & Kiehl, 2002), which is strongly related to the sea surface temperature (SST) pattern (Zhang & Dong, 2004). During the extended boreal winter (November-April), the MJO is more active with the eastward propagation across the Indo-Pacific warm pool as well as southward propagation toward the South Pacific Convergence Zone (SPCZ; Wheeler & Hendon, 2004). In contrast, during the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In addition, tropical rainfall is produced by different cloud and storm systems, such as monsoon depressions, typhoons (hurricanes), mesoscale convective systems and the Madden-Julian oscillation. Some pioneering studies have been done for the annual cycle changes of typhoons/hurricanes (Shan et al 2023) and Madden-Julian Oscillation (Bui and Hsu 2023) and definitely more researches are needed in the future. Quantifying rainfall changes requires understanding the contributions of different storm types to the tropical rainfall annual cycles and how they respond to global warming.…”
Section: Quantificationmentioning
confidence: 99%
“…In addition, tropical rainfall is produced by different cloud and storm systems, such as monsoon depressions, typhoons (hurricanes), mesoscale convective systems and the Madden-Julian oscillation. Some pioneering studies have been done for the annual cycle changes of typhoons/hurricanes (Shan et al 2023) and Madden-Julian Oscillation (Bui and Hsu 2023) and definitely more researches are needed in the future. Quantifying rainfall changes requires understanding the contributions of different storm types to the tropical rainfall annual cycles and how they respond to global warming.…”
Section: Quantificationmentioning
confidence: 99%
“…Because of their strong societal impacts, much research has been done to determine if the MJO and TCs are intensifying in our warming climate. Multiple studies have shown that the MJO has intensified during the last century [16][17][18][19], and many models predict that MJO rainfall and/or circulations will increase during the rest of the 21st century [20][21][22][23][24][25][26][27][28], although some climate models predict little or no additional MJO intensification [29]. Observations suggest that while global TCs have become fewer in number in recent decades, storms have intensified more rapidly as the oceans have warmed, with a greater proportion reaching category 4 or 5 strength [30].…”
Section: Introductionmentioning
confidence: 99%